Especificación formal de arquitecturas de software basadas en componentes: chequeo de corrección con cálculo −Parq - Diosa, Henry Alberto; Díaz Frías, Juan Francisco; Gaona Cuevas, Carlos Mauricio (Revista Científica, 2011)
In this paper we describe a correctness checking formal method of reference architectures against reference models in a component-based software development perspective. These models are specified by means of ρarq − calculus. We use two formal tools; the first, the concept of Labelled Transition System (LTS) enhanced with the conditional-transition concept for logical variables whose resolution may be obtained from a global store of constraints. The second, the observation equivalence theory proposed by Robin Milner and his collaborators in Cambridge University.